2020
DOI: 10.1177/2045894019873545
|View full text |Cite
|
Sign up to set email alerts
|

Real‐life data of direct anticoagulant use, bleeding risk and venous thromboembolism recurrence in chronic thromboembolic pulmonary hypertension patients: an observational retrospective study

Abstract: Introduction Lifelong anticoagulation is the cornerstone of the chronic thromboembolic pulmonary hypertension (CTEPH) treatment regardless of the additional pulmonary endarterectomy, balloon pulmonary angioplasty, or medical treatment alone. Aim of this study was to evaluate the rate of oral anticoagulant preferences and document direct oral anticoagulants’ (DOACs’) safety, efficacy in the CTEPH population. Methods Patients’ demographic data obtained from database between September 2011 and April 2018. In-hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…9 Other studies in CTEPH have reported similar or lower bleeding rates with NOACs than with VKAs, while results for venous thromboembolism recurrence have been inconsistent. 7,10,11 Our results show similar absolute and exposure-adjusted rates of hemorrhagic events with VKAs and NOACs, while exposure-adjusted rates of embolic/thrombotic events were higher with NOACs. However, the numbers of events were small and the excess of embolic/thrombotic events could be a chance observation or related to differences in baseline characteristics between the two groups.…”
supporting
confidence: 51%
“…9 Other studies in CTEPH have reported similar or lower bleeding rates with NOACs than with VKAs, while results for venous thromboembolism recurrence have been inconsistent. 7,10,11 Our results show similar absolute and exposure-adjusted rates of hemorrhagic events with VKAs and NOACs, while exposure-adjusted rates of embolic/thrombotic events were higher with NOACs. However, the numbers of events were small and the excess of embolic/thrombotic events could be a chance observation or related to differences in baseline characteristics between the two groups.…”
supporting
confidence: 51%
“…It demonstrates that BPA treatment improved the exercise capacity, oxygenation, NT pro-BNP levels, and haemodynamics of patients with inoperable or residual or recurrent CTEPH. Patients with inoperable or residual CTEPH are often treated with riociguat, which is approved for CTEPH therapy, or other PAH-specific drugs [14]. Riociguat improves haemodynamics, with a 10% decrease in mPAP, a 33% decrease in PVR, and a 10% increase in 6MWD [15].…”
Section: Discussionmentioning
confidence: 99%
“…This study used direct oral anticoagulants (DOACs) in most patients, although this is not recommended by the current guidelines. However, a recent report [14] indicated that DOACs could be a safe and effective alternative to warfarin treatment in CTEPH patients. This may be especially important for patients with limited access to health care facilities and noncompliance issues.…”
Section: Discussionmentioning
confidence: 99%
“…Although warfarin was recommended as the treatment of choice, direct oral anticoagulants (DOACs) have been alternatively used considering their proven therapeutic effects in VTE and administrative convenience over warfarin. Recently, several studies have reported the efficacy and safety of anticoagulants including warfarin and rivaroxaban in CTEPH patients (5)(6)(7)(8)(9). However, these studies failed to identify the differences in anticoagulation outcomes between CTEPH patients with and without prior VTE history.…”
Section: Introductionmentioning
confidence: 99%